Peningkatan Kualitas Layanan dan Kinerja Karyawan Melalui Evaluasi Program Pelatihan pada Bank BJB Cabang Surabaya - Lutfiyana, Rana Ardelia; Handayani, Wiwik (Education and Talent Development Center of Indonesia, 2025)
BJB Darmo Branch, Surabaya, regularly organizes training through BJB University and conducts digital-based performance evaluations through the BJB Prestasiku platform. However, the effectiveness of the training has not been thoroughly evaluated. This service activity aims to evaluate the impact of training on service quality and employee performance, as well as provide recommendations and initial assistance for implementing improvements. The method used is a descriptive quantitative approach with data collection techniques through direct observation, standardized questionnaires filled out by 30 active employees, and informal interviews. The results of the analysis showed that the training had a positive contribution to improving service quality and performance, although most participants considered the training materials to be too general and not fully relevant to their daily tasks. Based on these findings, strategic recommendations were developed that included adjusting training materials based on work division, conducting a training needs survey, and providing post-training reflection sessions. Initial assistance was conducted through informal communication and follow-up monitoring, including internal socialization activities by management. This activity is expected to be the basis for improving the training system to be more relevant, adaptive, and have a real impact on improving the quality of human resources within Bank BJB Darmo Branch.